Matematyka
nati677
2017-06-25 07:42:24
wyłącz wspólny czynnik przed nawiasem a) (7x-8)+(5x-3)= b) (-4a-5)+(-3a+7) = c) (-2,8x* -4)+(5x*-0,3) =
Odpowiedź
krysztof120
2017-06-25 12:52:35

Wyłącz wspólny czynnik przed nawiasem  a) (7x-8)+(5x-3)= 7x - 8 + 5x - 3 = 12x - 11 b) (-4a-5)+(-3a+7) = -4a - 5 - 3a + 7 = -7a + 2 c) (-2,8x* -4)+(5x*-0,3) = 11,2x - 1,5

patrycja285
2017-06-25 12:53:50

a) (7x-8)+(5x-3)=7x-8+5x-3=12x-11 b) (-4a-5)+(-3a+7)=-4a-5-3a+7=-7a+2 c) (-2,8x*-4)+(5x*-0,3)=-2,8x*-4+5x*-0,3=2,2x*-4,3

Dodaj swoją odpowiedź